2003
DOI: 10.2174/0929867033457674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the Plasmodium Falciparum Parasite Aspartic Protease Plasmepsin II As Potential Antimalarial Agents

Abstract: Malaria is a very serious infectious disease against which the currently available drugs are loosing effectiveness. The main problem is the emergence and the spreading of resistant parasite strains. New treatments are needed in order to regain control over the disease. Drug discovery efforts towards this goal are likely to be more successful, if they focus towards novel mechanisms of action. Such efforts will result in drugs that are functionally and structurally different from the existing drugs and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 0 publications
1
113
1
4
Order By: Relevance
“…Rather, our data suggest that pepstatin A is not effective on WT parasites because blockade of plasmepsins is not lethal. Dozens of laboratories have made hundreds of compounds targeted to plasmepsins (25). None is more potent than pepstatin A against isolated enzyme, and all show limited efficacy on cultured parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, our data suggest that pepstatin A is not effective on WT parasites because blockade of plasmepsins is not lethal. Dozens of laboratories have made hundreds of compounds targeted to plasmepsins (25). None is more potent than pepstatin A against isolated enzyme, and all show limited efficacy on cultured parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts discoveries will result in new drugs that are functionally and structurally different from the existing drugs and therefore will overcome existing resistances. Here we have focused on the aspartic protease Plasmepsin II, which is a promising new drug target [4]. Several x-ray structures of PM II have been described previously, but thus far, structure-based drug design has been hampered by the fact that only inhibitors comprising a statine moiety or derivatives thereof have been published.…”
Section: Figurementioning
confidence: 99%
“…Of those four, P. falciparum accounts for over 95% of all malaria cases, mainly in Africa, and children under 5 years of age are among the most vulnerable to malaria infection [1]. It has been shown that hemoglobin catabolism, which takes place in an acidic food vacuole, is essential for parasite survival, both in culture and in animal models [2][3][4]. Besides asparticproteases, three cysteine proteases (falcipain-1, -2, and -3) and one metalloprotease (falcilysin) have also been identified to digest hemoglobin in the food vacuole [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%